The anatomical location shapes the immune infiltrate in tumors of same etiology and affects survival - Santegoets, Saskia J. A. M.; Charoentong, Pornpimol (Clinical cancer research, 2019)
Purpose: The tumor immune microenvironment determines clinical outcome. Whether the original tissue in which a primary tumor develops influences this microenvironment is not well understood. - Experimental Design: We applied high-dimensional single-cell mass cytometry [Cytometry by Time-Of-Flight (CyTOF)] analysis and functional studies to analyze immune cell populations in human papillomavirus (HPV)-induced primary tumors of the cervix (cervical carcinoma) and oropharynx (oropharyngeal squamous cell carcinoma, OPSCC). - Results: Despite the same etiology of these tumors, the composition and functionality of their lymphocytic infiltrate substantially differed. Cervical carcinoma displayed a 3-fold lower CD4:CD8 ratio and contained more activated CD8+CD103+CD161+ effector T cells and less CD4+CD161+ effector memory T cells than OPSCC. CD161+ effector cells produced the highest cytokine levels among tumor-specific T cells. Differences in CD4+ T-cell infiltration between cervical carcinoma and OPSCC were reflected in the detection rate of intratumoral HPV-specific CD4+ T cells and in their impact on OPSCC and cervical carcinoma survival. The peripheral blood mononuclear cell composition of these patients, however, was similar. - Conclusions: The tissue of origin significantly affects the overall shape of the immune infiltrate in primary tumors.
published first September 17, 2018
Gesehen am 17.05.2019